ОСОБЛИВОСТІ УЯВЛЕНЬ ДІТЕЙ П ЯТОГО – СЬОМОГО РОКІВ ПРО ЧАС – ПРОСТІР ЖИТТЯ - Кононко, О. Л. (Видавництво НДУ ім. М. Гоголя, 2023)
Стаття присвячена дослідженню актуальної проблеми особливостей усвідом- лення дітьми старшого дошкільного віку свого життя як часо – просторової реальності. На основі аналізу сучасної психолого-педагогічної літератури розглянуто поняття «самосвідомість», «життєдіяльність», охарактеризовано категорії «особистісне буття», «суб’єкт життєдіяльності», «суб’єкт самосвідомості». У статті зазна- чено, що показниками прогресивного розвитку самосвідомості на етапі дошкільного дитинства виступають адекватні й узагальнені уявлення про світ і своє місце в ньому та система цінностей. Розкрито суть ключового поняття «уявлення дошкільників про час і простір життя», яке тлумачиться як образне відображення у дитячій свідомості відносин з природним, предметним, соціальним середовищем та власним «Я». Визначено критерії оцінки особливостей сформованості у дітей п’ятого – сьомого років життя світоглядних уявлень, а саме: домінантні цінності, на які орієнтувалися до- сліджувані; ступінь їх узагальненості та образності; продуктивність та аргумен- тованість актуалізації уявлень про життєдіяльність та власну активність в ній. Описано авторську типологію критеріїв оцінки, до складу якої увійшли чотири типи: світоглядно-духовний, соціально-унормований, прагматичний та гедо- ністичний. Визначено основні психолого-педагогічні умови ефективного збагачення дитячих уявлень про життя та власне «Я», до яких належать: формування статевої свідомості та статеворольової поведінки; розвиток ціннісного самоставлення, почуття власної гідності, елементарних форм рефлексії; сприяння усвідомленню дітьми дошкільного віку динаміки власного життя та її ролі у розвитку особистості. Накреслено перспективні напрями подальшої роботи з розробки моделі розвитку у дошкільників ціннісного ставлення до життя та власного «Я» і його методичного забезпечення.
Introduction. The problem of diagnosis and development of children in the fifth and seventh years of life adequate ideas about life, its meaning, features of dynamics and their own subjective position remains relevant due to the shortage of domestic psychological – pedagogical work in this field; the importance of diagnostic methods and typology of ideas of children of this age about life and the actual "I" for modern scientists and educators. The article is devoted to the disclosure of the content, criteria for assessing children s ideas about life and themselves as its active subjects, a description of the author s method of diagnosing the phenomenon under study and the developed typology. The materials of the article actualize the importance of a holistic approach to the study of the peculiarities of the ideas of children of five or seven years of life and the nature of activity in it of their own "I" and presents psychological and pedagogical conditions for optimizing the educational process. Methods: analysis and generalization of data of philosophical and psychological – pedagogical literature on the researched problem; theoretical modeling for construction of diagnostic research methods; observations, individual conversations. Results. The most important results of the research are: levels of their individual – age "top" – the highest personal level. 2 Development and description of the author s diagnostic method for determining the characteristics of preschoolers ideas about life and their place in it. 3. Implementation of qualitative and quantitative analysis of empirical data of the ascertaining stage of the study. 4. Development of criteria for assessing the degree of formation in children of five or seven years of ideas about the essence and meaning of life, their own subjective activity The main criteria include: leading values, which are the focus of research in the process of life; the degree of their generalization and adequacy; productivity and argumentation of the child s actualization of ideas about life and their own activity in it. 5. Creating an author s typology of the picture of the world and self-image as a set of ideas that guide the child in life. It includes four main types: ideological and spiritual, socially normalized, pragmatic and hedonistic. 6. Determining the psychological and pedagogical conditions for optimizing the educational process in preschool education in order to lay the foundations of active in form and moral in content life position "I am in the world". Originality. For the first time: the concept of "personal life of a preschooler" is qualified; developed a toolkit of diagnostic procedures aimed at studying the specifics of the development of self-awareness; the criteria for assessing the peculiarities of the formation of children s fifth-seventh years of ideas about life, the dynamics of its development, the nature of their inherent subjective activity; the author s typology of ideas of children of the specified age about life and the place in it is created; the complex of psychological and pedagogical conditions of optimization of educational process in ZDO for the purpose of enrichment of representations of preschool children about the world and actually "I" is substantiated, Conclusions. The ideas of children of the fifth and seventh years about the time and space of life are qualified as a reflection of the consciousness of the relationship with the natural, material, social environment and their own "I". The image of the world and the self-image of the subjects are analyzed through the prism of past-present and future times. Criteria for assessing the degree of formation of children s ideas about life and their own subjective activity were: leading values, the degree of their generalization and adequacy, productivity and argumentation of the actualization of ideas. The author s typology of children s ideas about life and the "I" is characterized, which includes four types: ideological and spiritual, socially normalized, pragmatic and hedonistic. The basic psychological and pedagogical conditions of effective enrichment of children s ideas are determined: the formation of sexual consciousness and gender-role behavior; development of value self-esteem, self- esteem, elementary forms of reflection; promoting children s awareness of the dynamics of their own lives and its role in personal development.